The AI-Dependent Learning Phenomenon Exploring Students’ Dependence on AI in Completing College Academic Task - SH, Khaerun Nisa; Sahade; Mufaridho, Lailatul Maziyah Wildan (International Journal of Education, Vocational and Social Science, 2026)
This study investigates the emerging phenomenon of AI-dependent learning among university students, focusing on how reliance on generative artificial intelligence tools shapes their academic behaviors, learning motivation, and engagement with course tasks. The rapid advancement of AI applications, such as ChatGPT, has transformed students’ study habits, yet concerns arise regarding excessive reliance that may weaken independent cognitive processes. Using a qualitative descriptive method, this research involved 30 accounting students from State University of Makassar. Participants were selected through purposive sampling to ensure they had substantial exposure to AI-assisted academic work. The findings indicate that AI dependence is commonly driven by academic workload, tight deadlines, a desire for efficiency, and the perception that AI provides faster and higher-quality output. However, overreliance leads to diminished critical thinking, reduced confidence in completing tasks independently, and concerns related to academic integrity. This study highlights the urgent need for universities to establish AI literacy guidelines, promote responsible use, and design learning activities that balance technological assistance with genuine cognitive engagement.